(untitled) (Istituto Lombardo - Accademia di Scienze e Lettere • Incontri di Studio, 2018)
Following development of pharmacological science in the last three decades, we started with brain studies aimed to characterize the role of serotonin and dopamine systems in feeding behaviour, by using traditional pharmacological approaches, such as injection of stimulatory and/or inhibitory drugs and monitoring the consequent behavioral changes. Then, we tried more physiological approaches to study serotonin system, by modulating its effects through special diets, thus proposing a new concept in nutritional pharmacology, in particular in the treatment of feeding disorders. Then, we focused to the study of obesity, by highlighting the multi-factorial approaches that, in addition to drugs, require an integration of other biological and psychological dimension, such as life style changes and cultural education, in treatment of this and related disorders.